Readiness of Retirement Based on Gender, Position and Family Social Support - Wia Septia; Herman Nirwana; Afdal Afdal (Universitas Negeri Padang, 2020)
Readiness for retirement based on sex, position and family social support and its implications for Guidance and Counseling services. This study aims to describe the readiness to face retirement in civil servants in terms of sex, position and family social support. The sample used in this study were 40 civil servants who would retire in various government agencies in Padang Panjang City, West Sumatra. This research uses Proportional Random Sampling technique. The instrument used in this study was a scale of readiness retirement with a reliability of 0.893 and a scale of family social support with a reliability of 0.941. The findings show that there is no difference in readiness retirement in terms of sex, position and family social support. This shows that there are other factors that can affect a person's retirement readiness. These factors are age, education level, race, ethnicity and personality. Self-efficacy is a personality dimension which is an individual's assessment of his or her ability or competence to do a task, achieve a goal, and produce something.